Percutaneous access for endovascular aortic aneurysm repair: A systematic review and meta-analysis. (December 2016) - Hajibandeh, Shahin; Hajibandeh, Shahab; Antoniou, Stavros A; Child, Emma; Torella, Francesco; Antoniou, George A
Purpose: Our objective was to undertake a comprehensive review of the literature and conduct an analysis of the outcomes of percutaneous endovascular aneurysm repair. Methods: MEDLINE; EMBASE; CINAHL; CENTRAL; the World Health Organization International Clinical Trials Registry; ClinicalTrials.gov; and ISRCTN Register, and bibliographic reference lists were searched to identify all studies providing comparative outcomes of the percutaneous technique for endovascular aneurysm repair. Success rate and access-related complications were defined as the primary outcome parameters. Combined overall effect sizes were calculated using fixed effect or random effects models. We conducted a network meta-analysis of different techniques for femoral access applying multivariate meta-analysis assuming consistency. Findings: Three randomised controlled trials and 18 observational studies were identified. Percutaneous access was associated with a lower frequency of groin infection ( p < 0.0001) and lymphocele ( p = 0.007), and a shorter procedure time ( p < 0.0001) and hospital length of stay ( p = 0.03) compared with open surgical access. Moreover, percutaneous endovascular aneurysm repair did not increase the risk of haematoma, pseudoaneurysm, and arterial thrombosis or dissection. Conclusion: Percutaneous access demonstrates advantages over conventional surgical exposure for endovascular aneurysm repair, as indicated by access-related complications and hospital length of stay. Further research is required to define its impact on resource utilization, cost-effectiveness and quality of life.